HAKIM TIRMIDHI AND THE THEORY OF DIVINE LOVE - Turopova Nodira Ilhom’s Qizi (Western European Studies, 2024)
In this article, Hakim Tirmidhi, one of the most eminent representatives of the Islamic world, and his thoughts on divine love, which is the main goal of Sufism, and its signs, are described based on some of his works.
Keywords: Hakim Tirmidhi; divine love; remembrance; contemplation